2009
DOI: 10.1159/000264923
|View full text |Cite
|
Sign up to set email alerts
|

RANTES in Exhaled Breath Condensate of Allergic Asthma Patients with Exercise-Induced Bronchoconstriction

Abstract: Background: The response of asthmatics to exercise differs from that of healthy subjects, and the mechanisms responsible for exercise-induced bronchoconstriction (EIB) remain to be elucidated. Objectives: The aim of this study was to evaluate changes in RANTES levels in exhaled breath condensate (EBC) following intensive exercise in allergic asthmatics. Methods: The study was conducted in a group of 19 asthmatics (11 with EIB and 8 without EIB) and 7 healthy volunteers. Changes in the concentrations of RANTES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…R2 peptide also prevented airway tissue remodelling by reducing the increased goblet cell hyperplasia, collagen deposition and imbalance of MMPs and TIMPs. The migration of inflammatory cells from blood into the airway occurs through binding to specific adhesion molecules such as VCAM-1 and chemokines such as CCL5 and IL-8 (Berkman et al, 1996;Zietkowski et al, 2009). VCAM-1 expression is enhanced by Th2-mediated cytokines such as IL-4, IL-13 and TNF-a (Sriramarao et al, 2000;Wills-Karp and Karp, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…R2 peptide also prevented airway tissue remodelling by reducing the increased goblet cell hyperplasia, collagen deposition and imbalance of MMPs and TIMPs. The migration of inflammatory cells from blood into the airway occurs through binding to specific adhesion molecules such as VCAM-1 and chemokines such as CCL5 and IL-8 (Berkman et al, 1996;Zietkowski et al, 2009). VCAM-1 expression is enhanced by Th2-mediated cytokines such as IL-4, IL-13 and TNF-a (Sriramarao et al, 2000;Wills-Karp and Karp, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…EIA and EIB are usually defined on the basis of a fall of 1 10% from baseline FEV 1 after a standardized exercise challenge test [6] . The pathogenesis of EIA and EIB remains elusive, although evidence points to dehydration of the airways with eosinophil and mast cell degranulation as central mechanisms behind the phenomenon [7][8][9] , increasing both bronchial muscle constriction and blood vessel dilatation. The latter could be the explanation for an increase in EBT and would possibly be even more pronounced in subjects with concomitant airway inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies we observed that in asthmatic patients, as a consequence of postexercise bronchoconstriction, increased expression of RANTES in the airways occurs [8]. This process, by promoting the migration and activation of inflammatory cells including eosinophils, may play an important role in upregulation of the airway inflammation observed after EIB in asthmatic patients.…”
Section: Introductionmentioning
confidence: 95%